Horrible combinatoric summation

Algebra Level 5

Given A , B A,B that A = k = 0 2019 ( m = 0 k ( 2020 m ) ) ( l = k + 1 2020 ( 2020 l ) ) B = k = 0 2020 ( 2020 k ) 2 A=\sum_{k=0}^{2019} \left(\sum_{m=0}^k \binom{2020}{m} \right)\left(\sum_{l=k+1}^{2020} \binom{2020}{l}\right) \\ B= \sum_{k=0}^{2020} \binom{2020}{k}^2 Find A B \dfrac{A}{B} .


The answer is 1010.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hypergeo H.
Apr 14, 2020

A = k = 0 n 1 m = 0 k l = k + 1 n ( n m ) ( n l ) = l = 1 n m = 0 l 1 k = m l 1 ( n m ) ( n l ) ( 0 m k l 1 n 1 ) = l = 1 n m = 0 l 1 ( l m ) ( n m ) ( n l ) = l = 1 n r = 1 l r ( n l r ) ( n l ) ( r = l m ) = r = 1 n r l = r n ( n l r ) ( n n l ) = r = 1 n r ( 2 n n r ) ( Vandermonde ) = n 2 ( 2 n n ) ( see Note ) B = k = 0 n ( n k ) 2 = k = 0 n ( n k ) ( n n k ) = ( 2 n n ) ( Vandermonde ) A B = n 2 = 1010 ( n = 2020 ) \begin{aligned} A&=\sum_{k=0}^{n-1}\sum_{m=0}^k\sum_{l=k+1}^n \binom nm \binom nl\\ &=\sum_{l=1}^n \sum_{m=0}^{l-1}\sum_{k=m}^{l-1} \binom nm \binom nl &&\small (0\;\leqslant\; m\;\leqslant\; k\;\leqslant\; l-1\;\leqslant\; n-1)\\ &=\sum_{l=1}^n \sum_{m=0}^{l-1} (l-m)\binom nm \binom nl\\ &=\sum_{l=1}^n \sum_{r=1}^l r\binom n{l-r} \binom nl &&\small(r=l-m)\\ &=\sum_{r=1}^n r\sum_{l=r}^n\binom n{l-r} \binom n{n-l}\\ &=\sum_{r=1}^n r\binom {2n}{n-r} &&\small(\text{Vandermonde})\\ &=\frac n2 \binom {2n}n &&\small(\text{see Note})\\\\ B&=\sum_{k=0}^n\binom{n}k^2 \\ &=\sum_{k=0}^n\binom{n}k\binom {n}{n-k} \\ &=\binom {2n}n &&\small(\text{Vandermonde})\\\\ \therefore \frac AB &= \frac n2 =\color{#D61F06}{1010} &&\small(n=2020) \end{aligned}


Note:
r = 1 n r ( 2 n n r ) = r = 1 n r ( 2 n n + r ) = 1 2 r = 1 n ( n + r ) ( 2 n n r ) ( n r ) ( 2 n n + r ) = 1 2 r = 1 n 2 n ( 2 n 1 n r ) 2 n ( 2 n 1 n + r ) = 2 n 2 r = 1 n ( 2 n 1 n r ) r = 1 n 1 ( 2 n 1 n r 1 ) = 2 n 2 [ r = 1 n ( 2 n 1 n r ) r = 2 n ( 2 n 1 n r ) ] = 2 n 2 ( 2 n 1 n 1 ) = n 2 ( 2 n n ) \small \begin{aligned} &\qquad \sum_{r=1}^n r\binom {2n}{n-r} \color{grey}{=\sum_{r=1}^n r\binom {2n}{n+r}}\\ &=\frac 12 \sum_{r=1}^n (n+r)\binom {2n}{n-r}-(n-r)\binom {2n}{n+r}\\ &=\frac 12 \sum_{r=1}^n 2n\binom {2n-1}{n-r}-2n\binom {2n-1}{n+r}\\ &=\frac {2n}2 \sum_{r=1}^n \binom {2n-1}{n-r}-\sum_{r=1}^{n-1} \binom {2n-1}{n-r-1}\\ &=\frac {2n}2\left[\sum_{r=1}^n \binom {2n-1}{n-r} - \sum_{r=2}^n \binom {2n-1}{n-r} \right]\\ &=\frac {2n}2\binom {2n-1}{n-1}\\ &=\frac n2 \binom {2n}n\\ \end{aligned}

Mark Hennings
Nov 5, 2019

Let N N N \in \mathbb{N} . For any 0 u N 0 \le u \le N , the sum C N , u = m = 0 u ( N m ) ( N u m ) C_{N,u} \; = \; \sum_{m=0}^u \binom{N}{m}\binom{N}{u-m} is the coefficient of X u X^u in the polynomial ( 1 + X ) N × ( 1 + X ) N = ( 1 + X ) 2 N (1+X)^N \times (1+X)^N \; = \; (1 + X)^{2N} , and hence C N , u = ( 2 N u ) 0 u N C_{N,u} \; =\; \binom{2N}{u} \hspace{2cm} 0 \le u \le N In particular we see that B N = k = 0 N ( N k ) 2 = k = 0 N ( N k ) ( N N k ) = C N , N = ( 2 N N ) B_N \; = \; \sum_{k=0}^N \binom{N}{k}^2 \; = \; \sum_{k=0}^N \binom{N}{k}\binom{N}{N-k} \; = \; C_{N,N} \; = \; \binom{2N}{N} On the other hand A N = k = 0 N 1 ( m = 0 k ( N m ) ) ( = k + 1 N ( N ) ) = m = 0 N 1 = m + 1 N k = m 1 ( N m ) ( N ) = m = 0 N 1 = m + 1 N ( m ) ( N m ) ( N ) = m = 0 N 1 = m + 1 N ( m ) ( N m ) ( N N ) = m = 0 N 1 = 0 N 1 m ( N m ) ( N m ) ( N ) = u = 0 N 1 ( N u ) m = 0 u ( N m ) ( N u m ) = u = 0 N 1 ( N u ) C N , u = u = 0 N 1 ( N u ) ( 2 N u ) = 1 2 u = 0 N 1 ( ( 2 N u ) u ) ( 2 N u ) = 1 2 [ u = 0 N 1 ( 2 N ) ! u ! ( 2 N 1 u ) ! u = 1 N 1 ( 2 N ) ! ( u 1 ) ! ( 2 N u ) ! ] = 1 2 [ u = 0 N 1 ( 2 N ) ! u ! ( 2 N 1 u ) ! u = 0 N 2 ( 2 N ) ! u ! ( 2 N 1 u ) ! ] = ( 2 N ) ! 2 ( N 1 ) ! N ! = 1 2 N ( 2 N N ) \begin{aligned} A_N & = \; \sum_{k=0}^{N-1} \left(\sum_{m=0}^k \binom{N}{m}\right)\left(\sum_{\ell=k+1}^N\binom{N}{\ell}\right) \; = \; \sum_{m=0}^{N-1}\sum_{\ell=m+1}^N \sum_{k=m}^{\ell-1}\binom{N}{m}\binom{N}{\ell} \; = \; \sum_{m=0}^{N-1}\sum_{\ell=m+1}^N (\ell - m)\binom{N}{m}\binom{N}{\ell} \\ & = \; \sum_{m=0}^{N-1}\sum_{\ell=m+1}^N (\ell - m)\binom{N}{m}\binom{N}{N - \ell} \; = \; \sum_{m=0}^{N-1}\sum_{\ell=0}^{N-1-m} (N - m - \ell)\binom{N}{m}\binom{N}{\ell} \; = \; \sum_{u=0}^{N-1} (N-u)\sum_{m=0}^u \binom{N}{m}\binom{N}{u-m} \\ & = \; \sum_{u=0}^{N-1}(N-u)C_{N,u} \; = \; \sum_{u=0}^{N-1}(N-u)\binom{2N}{u} \; = \; \frac12\sum_{u=0}^{N-1}\big((2N-u) - u\big)\binom{2N}{u} \\ &= \; \frac12\left[\sum_{u=0}^{N-1} \frac{(2N)!}{u! (2N-1-u)!} - \sum_{u=1}^{N-1} \frac{(2N)!}{(u-1)!(2N-u)!}\right] \; = \; \frac12\left[\sum_{u=0}^{N-1} \frac{(2N)!}{u! (2N-1-u)!} - \sum_{u=0}^{N-2} \frac{(2N)!}{u!(2N-1-u)!}\right] \; = \; \frac{(2N)!}{2(N-1)! N!} \\ & = \; \frac12N\binom{2N}{N} \end{aligned} so that A N B N = 1 2 N \frac{A_N}{B_N} \; = \; \frac12N In the case N = 2020 N=2020 , we obtain the answer 1010 \boxed{1010} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...